Personalised Health Care, the need for reassessment. A HTA perspective far beyond cost-effectiveness (Italian Journal of Public Health, 2012)
Background: personalised health care has been claimed to play an outstanding role in the future health services. In fact, health care systems will have to face changes in their work flows and processes due to the implementation of personalised technologies. Health Technology Assessment provides information to decision makers at any level on the introduction and exclusion of health technologies from the health care systems.Methods: the definition of Health Technology Assessment (HTA) and the concepts and questions raised in the EUnetHTA core model, were used as a framework to analyse the impact of these new services in health care provision.Results: personalised health care services and products are health technologies, mainly diagnostics that have a broad impact in the health care systems. Although, safety, clinical effectiveness and economical aspects and consequences have been described, ethical, social and organisational issues raised questions that should be answered before considering their implementation in the health systems. Special attention should be paid on new requirements for regulation, data protection and the empowerment of citizen and health professionals.Conclusions: the benefits and harms of personalised health-care technologies should be decided on a “case by case” rather than a “one size fits all” basis and has to be analysed under its many aspects. The combination of genetic, clinical and environmental factors is crucial for the correct understanding of personalised medicine and its implementation. Personalised health care will require a fine-tuned revision of existing HTA and Pharmacoeconomic’s guidelines to address its characteristics.
Keywords: HTA; Personalised Health Care